The Influence of Device Compatibility and IoT System Architecture on Adoption Rate and Usability in the Implementation of Smart Homes in Modern Housing in Tangerang - Soelistianto, Farida Arinie; Lesmana, Tera; Fildansyah, Rully (West Science Social and Humanities Studies, 2025)
This study investigates the influence of device compatibility and IoT system architecture on adoption rates and ease of use in smart home implementation within modern housing developments in Tangerang, Indonesia. Employing a quantitative research approach, data were collected from 125 respondents using a structured questionnaire measured on a five-point Likert scale. The data were analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to test the relationships among constructs. The results reveal that both device compatibility and IoT system architecture significantly and positively influence ease of use, which in turn mediates their effects on adoption rates. A robust IoT system architecture enhances interoperability and system responsiveness, improving user perceptions of convenience and reliability. The findings underscore that technical design and user-centric system integration jointly determine the success of smart home adoption. This research contributes to extending the Technology Acceptance Model (TAM) within the IoT context and offers practical implications for developers, policymakers, and housing planners in fostering inclusive and sustainable smart living environments in Indonesia.